Antecedents of customer retention in Malaysian retail stores - Sayyedeh Parisa Saeidi, 1976-, author; Amran Md. Rasli, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2019